The Impact of Human Resource Management Practices on Organizational Agility Through Knowledge Management Processes as an Intermediate Variable - Ebrahim, Ahmed (The Arab Journal of Administration, 2021)
This research aimed to determine the type and degree of strength of the indirect relationship between human resource management practices and organizational agility in Menoufia University through knowledge management processes as an intermediate variable. To achieve this goal, a survey list was developed to collect the required data from the sample, the size of which was determined (377 items). The survey list was sent over the internet to more than 600 employees in all university units, and 331 lists were answered, including 296 lists that are valid for analysis (78.5% of the sample size). The research reached a number of results, the most important of which was the presence of a strong, indirect, statistically significant relationship between human resource management practices and organizational agility in Menoufia University through knowledge management processes as an intermediate variable. At the end of this research, a number of recommendations were reached, the most important of which were: the necessity of increasing the interest of the officials of Menoufia University in activating the material and moral methods of workers motivating, and the necessity of their earnest endeavor to improve the level of organizational agility of the university; In order to increase its ability to adapt to the dynamic and turbulent environmental conditions, to reduce the threats that it faces or may face, and to exploit the available opportunities that may be available in the surrounding environment in the future.